Learning technical terms from the textbook vs learning technical terms from the technical dictionary - Abd.Manan, Amerrudin B. (Journal of Modern Languages, 2017)
This study was conducted to find out whether the technical dictionary is the better alternative than the specialised textbooks in learning technical vocabulary amongst students pursuing a major. Bearing in mind that technical vocabulary can also be learned from the textbook via lexical familiarisation devices, it was, however, earlier assumed that the technical dictionary may be a more effective tool to learning technical vocabulary in that every new term is normally carried and explained in dictionaries. Data for the study was obtained from a textbook sample derived from a set of 5 different introductory business textbooks for beginner undergraduates. The textbook sample comprises 500 explained terms, which comprise the first 100 terms from each textbook. Two business dictionaries were used in combination to check the textbook terms’ availability. The results of this study suggest that the texlbook may be superior to the technical dictionary in learning technical terms in the students’ major. Out of all the explained terms from the textbook sample, a quarter was not found in the technical dictionary, suggesting that students could be better off learning these terms via lexical familiarisation from the textbook itself.